2015
DOI: 10.1007/s12678-015-0267-9
|View full text |Cite
|
Sign up to set email alerts
|

First Insight into Fluorinated Pt/Carbon Aerogels as More Corrosion-Resistant Electrocatalysts for Proton Exchange Membrane Fuel Cell Cathodes

Abstract: International audienceThis study evaluates the fluorination of a carbon aerogel and gives first insights into its durability when used as platinum electrocatalyst substrate for proton exchange membrane fuel cell (PEMFC) cathodes. Fluorine has been introduced before or after platinum deposition. The different electrocatalysts are physico-chemically and electrochemically characterized, and the results discussed by comparison with commercial Pt/XC72 from E-Tek. The results demonstrate that the level of fluorinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 41 publications
0
16
1
Order By: Relevance
“…89 The synthesis protocol has been thoroughly described in earlier contributions of the authors. 77,90 Briefly, the two precursors, resorcinol (R, 99% C 6 H 6 O 2 , Alfa Aesar) and formaldehyde (F, 37 wt% CH 2 O in aqueous solution stabilized with 10-15 wt% methanol) were mixed with the sodium carbonate (C, 99.9999% Na 2 CO 3 , Sigma Aldrich) catalyst in deionized water with molar ratios F/R = 2, R/C = 200 and 5 wt% solid in solution. The resulting solution was then heated at T = 358 K under confined atmosphere for one week for gelation and mechanical handling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…89 The synthesis protocol has been thoroughly described in earlier contributions of the authors. 77,90 Briefly, the two precursors, resorcinol (R, 99% C 6 H 6 O 2 , Alfa Aesar) and formaldehyde (F, 37 wt% CH 2 O in aqueous solution stabilized with 10-15 wt% methanol) were mixed with the sodium carbonate (C, 99.9999% Na 2 CO 3 , Sigma Aldrich) catalyst in deionized water with molar ratios F/R = 2, R/C = 200 and 5 wt% solid in solution. The resulting solution was then heated at T = 358 K under confined atmosphere for one week for gelation and mechanical handling.…”
Section: Methodsmentioning
confidence: 99%
“…76 Recently, fluorination of carbon supports has also been proposed to prepare Pt-based electrocatalysts for oxygen reduction in PEMFC. 77 However, it has been shown that fluorination must be conducted prior to Pt deposition at the carbon substrate, as post-fluorination of a Pt/C electrocatalyst leads to deactivation of the Pt nanoparticles. Fluorination of the carbon support enables to bind fluorine atoms to their dangling groups, the latter likely being the ones that are oxidized first during PEMFC operation.…”
mentioning
confidence: 99%
“…There are indications that the fluorination of materials in acidic media improves their oxidative stability. Examples of such systems include Nafion ionomer, Pt/C, and platinum group metal-free catalysts for PEM fuel cells [ 30 , 31 , 32 ]. Recently, we also fluorinated a highly active FeN x -doped carbon catalyst in the hopes that fluorine would increase its stability in PEM fuel cells [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…This issue can be mitigated by "protecting" the carbon surface via appropriate surface treatments, e.g. metaloxides deposition [22] or fluorination [23]. Fluorination may have other advantageous effects regarding the physicochemical properties of the CA support, though.…”
Section: Introductionmentioning
confidence: 99%